Electrospun Antimicrobial Polyurethane Nanofibers Containing Silver Nanoparticles for Biotechnological Applications - Sheikh, Faheem A.; Barakat, Nasser A. M.; Kanjwal, Muzafar A.; Chaudhari, Atul A.; Jung, In-Hee; Lee, John Hwa; Kim, Hak Yong (Macromolecular research, 2009)
In this study, a new class of polyurethane (PU) nanofibers containing silver (Ag) nanoparticles (NPs) was synthesized by electrospinning. A simple method that did not depending on additional foreign chemicals was used to self synthesize the silver NPs in/on PU nanofibers. The synthesis of silver NPs was carried out by exploiting the reduction ability of N,N-dimethylformamide (DMF), which is used mainly to decompose silver nitrate to silver NPs. Typically, a sol-gel consisting of AgNO 3 /PU was electrospun and aged for one week. Silver NPs were created in/on PU nanofibers. SEM confirmed the well oriented nanofibers and good dispersion of pure silver NPs. TEM indicated that the Ag NPs were 5 to 20 nm in diameter. XRD demonstrated the good crystalline features of silver metal. The mechanical properties of the nanofiber mats showed improvement with increasing silver NPs content. The fixedness of the silver NPs obtained on PU nanofibers was examined by harsh successive washing of the as-prepared mats using a large amount of water. The results confirmed the good stability of the synthesized nanofiber mats. Two model organisms, E. coli and S. typhimurium , were used to check the antimicrobial influence of these nanofiber mats. Subsequently, antimicrobial tests indicated that the prepared nanofibers have a high bactericidal effect. Accordingly, these results highlight the potential use of these nanofiber mats as antimicrobial agents.